2020
DOI: 10.1038/s41550-020-01226-7
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the formation history of top-shaped asteroids from the surface boulder distribution

Abstract: Finding the basic mechanism governing the surface history of asteroids of various shapes is essential for understanding their origin and evolution. In particular, the currently visited asteroids (162173) Ryugu 1 and (101955) Bennu 2 by Hayabusa2 and OSIRIS-REx appear to be top-shaped. This distinctive shape, characterized by a raised equatorial bulge, is shared

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 31 publications
2
25
0
1
Order By: Relevance
“…At the surface region, when the interparticle friction and cohesion cannot counteract the increasing surface slopes owing to changes in the spin state of the body, local landslides would occur in this region and, thus, the regional morphology is modified. With a given friction angle, to sustain surface stability with increasing spins, a spherical body would evolve to an oblate shape with a raised equatorial bulge via surface landslides [190,191]. This kind of shape is often referred to as a "top" shape, as it resembles the spinning top toy.…”
Section: Spin-driven Structural Evolutionmentioning
confidence: 99%
“…At the surface region, when the interparticle friction and cohesion cannot counteract the increasing surface slopes owing to changes in the spin state of the body, local landslides would occur in this region and, thus, the regional morphology is modified. With a given friction angle, to sustain surface stability with increasing spins, a spherical body would evolve to an oblate shape with a raised equatorial bulge via surface landslides [190,191]. This kind of shape is often referred to as a "top" shape, as it resembles the spinning top toy.…”
Section: Spin-driven Structural Evolutionmentioning
confidence: 99%
“…These regolith layer activities highly depend on the dynamical environments near the surfaces of the asteroids, which are largely governed by the complicated geometries of the bodies and their irregular gravitational fields. Recent studies show the global patterns of the mass movements can decipher the surface evolutionary process and contribute to as-sessing the surface mechanical properties of small bodies [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…They derived the criteria of coexistence and transformation of static and flowing regolith regimes. Cheng et al [12] simulated the regolith migration driven by YORP spin-up employing discrete element method and observed that creeping granular materials moved from mid-high latitudes toward low latitudes and formed a pronounced equatorial bulge. Jawin et al [4] documented evidence of global patterns of mass movement on the surface of Bennu based on plenty of highresolution images taken by OSIRIS-REx cameras, unraveling the surface modification subject to regolith transport.…”
Section: Introductionmentioning
confidence: 99%
“…As examples of the latter microgravity regime, indeed the surfaces of both (101955) Bennu (Barnouin et al 2019) and (162173) Ryugu (Watanabe et al 2019) have been shown to be composed of loosely bound rubble. Many questions regarding the formation (Michel et al 2020;Cheng et al 2021), surface features (Shinbrot et al 2017;Bogdan et al 2020) and mechanical stability (Scheeres et al 2010;Sánchez & Scheeres 2020) of these asteroids still remain open.…”
Section: Introductionmentioning
confidence: 99%